Detectability and Usefulness of Automated Whole Breast Ultrasound in Patients with Suspicious Microcalcifications on Mammography: Comparison with Handheld Breast Ultrasound - Choi, Jae Jeong (J Breast Cancer, 2016)
PURPOSE: The purpose of this study was to prospectively evaluate the detectability and usefulness of automated whole breast ultrasound (AWUS) and to compare it with handheld breast ultrasound (HHUS) in cases with suspicious microcalcifications identified by mammography. METHODS: Forty-two patients with 43 suspicious microcalcifications (25 malignant and 18 benign) detected by mammography underwent AWUS, HHUS, and histol-ogic examination. With knowledge of the mammographic findings, HHUS was performed to assess the visibility of the microcalcifications and the presence of associated masses or ductal changes. Two radiologists reviewed the AWUS images in consensus using the same methods employed for HHUS. Detectability of AWUS was compared with that of HHUS and was correlated with histologic and mammographic findings. RESULTS: Of the 43 lesions, 32 (74.4%) were detectable by AWUS and 31 (72.1%) by HHUS. No significant differences in sensitivity were found between the two methods (p=0.998). AWUS detected 96% (24/25) of malignant microcalcifications and 44.4% (8/18) of benign microcalcifications. AWUS was more successful in the detection of malignant vs. benign lesions (96.0% vs. 44.4%, p=0.002), lesions >10 mm vs. ≤10 mm in size (86.7% [26/30] vs. 46.2% [6/13], p=0.009), lesions with a fine pleomorphic or linear shape vs. a round or amorphous or coarse heterogeneous shape (94.7% [18/19] vs. 58.3% [14/24], p=0.021), and lesions associated with a mass or architectural distortion vs. without obvious changes on mammography (100% [19/19] vs. 54.2% [13/24], p=0.022). CONCLUSION: Detectability of AWUS was comparable to that of HHUS in cases where suspicious microcalcifications were identified on mammography. Therefore, AWUS might be helpful in the performance of ultrasound-guided percutaneous procedures for highly suspicious microcalcifications.